2021
DOI: 10.21511/bbs.16(1).2021.08
|View full text |Cite
|
Sign up to set email alerts
|

The level of digital transformation affecting the competitiveness of banks

Abstract: The article examines the competitiveness of Ukrainian banks influenced by economy digitalization, the dynamic spread of electronic payments and e-commerce, as well as innovative technologies aimed at providing digital services. When shifting to an Online Platform business model, a bank can expand its range of banking products, attract more customers, thereby forming a competition policy and gaining competitive advantages. The paper aims to assess the digitalization level affecting the general competitiveness o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
9
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(13 citation statements)
references
References 20 publications
3
9
0
1
Order By: Relevance
“…Rajan (1992), B atiz-Lazo andWoldesenbet (2006), Acharya et al (2008), Zhao et al (2019) also found that digitalization helps increase bank efficiency and thus, improves bank's competitive positions. Based on these reasonings, a positive relationship between bank digitalization and profitability has been found in previous studies (see Carb o-Valverde et al (2020), Kriebel and Debener (2020), Malik et al (2020), Dadoukis et al (2021), Kolodiziev et al (2021), Do et al (2022)).…”
Section: Introductionsupporting
confidence: 56%
“…Rajan (1992), B atiz-Lazo andWoldesenbet (2006), Acharya et al (2008), Zhao et al (2019) also found that digitalization helps increase bank efficiency and thus, improves bank's competitive positions. Based on these reasonings, a positive relationship between bank digitalization and profitability has been found in previous studies (see Carb o-Valverde et al (2020), Kriebel and Debener (2020), Malik et al (2020), Dadoukis et al (2021), Kolodiziev et al (2021), Do et al (2022)).…”
Section: Introductionsupporting
confidence: 56%
“…Therefore, the results of this study succeeded in proving that banking digital transformationinfluence on competitive advantage and become one of the brilliant strategies in banking marketing. According to Kolodiziev et al (2021), currently, the digitalization process in banking is a way to expand the range of banking products and help shape competition policies and become a competitive advantage. According to Hadi & Hmood (2020) that the implementation of a digital transformation strategy by banks will provide many advantages.…”
Section: Discussionmentioning
confidence: 99%
“…The digital transformation process is considered as the use of digital technology to improve business models and increase their efficiency (Galazova & Magomaeva, 2019). Thus, digital transformation is represented as a factor that is applied to assess the competitiveness capacity of banks that are scientifically found (Kolodiziev, Krupka, Shulga, Kulchytskyy & Lozynska, 2021). Currently, the need for digital transformation in the banking industry is experiencing rapid progress .…”
Section: Digital Transformationmentioning
confidence: 99%
“…Different theories exist in the literature regarding the positive and negative consequences of digital transformation in society (Martins et Kwilinski et al, 2020). Some of these studies were directed at investigating the differential impact of digitalization on banking products and services from a customer-oriented perspective (Prokopenko et al, 2022), while others discussed digital shifts in the financial industry in general (Kolodiziev et al, 2021;Volosovych et al, 2021;Kolodiziev et al, 2022). At the other end of the spectrum of academic research, there is a discussion about the link between the digital divide and the level of economic development of regions (Deineko et al, 2022;Melnyk et al, 2022) or country macroeconomic stability (Petroye et al, 2020;Tiutiunyk et al, 2021;Wang et al, 2022).…”
Section: Literature Reviewmentioning
confidence: 99%